Apakah Kualitas Institusi Berpengaruh pada Arus Masuk FDI di ASEAN? - Septiantoro, Ali Akbar; Hasanah, Heni; Alexandi, Muhammad Findi; Nugraheni, Sri Retno Wahyu (Jurnal Ekonomi dan Pembangunan Indonesia, 2020)
This paper examines the impact of institutional quality (government effectiveness index, voice and accountability index, and political stability) and economic variables (Gross Domestic Product [GDP], inflation, trade openness, and gross fixed capital formation) on Foreign Direct Investment (FDI) inflows in ASEAN 2012–2016 by using panel data analysis. The obtained results indicate that economics variables have a greater impact on FDI than political stability indicator. Our findings also suggest that insignificant effect of democracy and institutional quality indicator on FDI caused by the high level of corruption in ASEAN which maybe has a crowding out effect to level of democracy and institutional quality.